THE INFLUENCE OF WORK MOTIVATION, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT SOCIAL SERVICES OFFICE IN KUPANG CITY WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Djaniar, Upik (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the effect of work motivation, work environment and work discipline simultaneously on employee performance with satisfaction as an intervening variable at the Social Services Office of Kupang City. In this study using a quantitative approach, the data of respondents through a set of questionnaires with a sample of 60 respondents who are employees of the Kupang City Social Services Office. The analytical test tool used is SmartPLS 3 with the SEM ( Structural Equation Modeling) analysis method. The research results show, (1) Motivation has no significant effect on job satisfaction (2) Work environment has a significant effect on job satisfaction (3) Work discipline has a significant effect on job satisfaction (4) Motivation has no significant effect on employee performance (5 ) Work environment has a significant effect on employee performance (6) Work discipline has a significant effect on employee performance (7) Job satisfaction has a significant effect on employee performance (8) Job satisfaction cannot significantly mediate motivational variables on employee performance (9) Satisfaction work can significantly mediate work environment variables on employee performance (10) Job satisfaction can significantly mediate work discipline variables on employee performance.